Pengaruh Kompetensi, Motivasi Kerja Dan Lingkungan Kerfja Terhadap Kinerja Guru Sma Negeri 15 Medan - rahmah Putri Lubis; Fajar Pasaribu; Zulaspan Tufty (CERED Indonesia Institute, 2021)
The purpose of this study was to determine the effect of competence, work motivation and work environment on the performance of teachers in SMA Negeri 15 Medan. This study uses a quantitative approach. The study population was all civil servant teachers who worked at SMA Negeri 15 Medan. The research sample was all civil servant teachers who worked in SMA Negeri, amounting to 65 people. The data analysis used was the Structural Equation Model (SEM) method with the Partial Least Square (PLS) method. The results of this study indicate that: (1) competence has a significant positive effect on performance with a value of 0.252 and P-Values of 0.025. (2). Work motivation has a significant positive effect on performance satisfaction with a value of 0.247 and P-values of 0.018. (3). The work environment has a significant positive effect on performance with a value of 0.493 and P-values of 0.000.